Role of the sympathetic nervous system in the control of the goitrogenic response in the rat - Pisarev, Mario Alberto; Cradinali, D. P.; Juvenal, Guillermo Juan; Vacas, M. I.; Barontini, M.; Boado, R. J. (1981)
Fil: Juvenal, Guillermo Juan Comisión Nacional de Energía Atómica; Argentina